Clinical and Imaging Features of Patients With Encephalitic Symptoms and Myelin Oligodendrocyte Glycoprotein Antibodies - Wang, Jingsi; Qiu, Zhandong; Li, Dawei; Yang, Xixi; Ding, Yan; Gao, Lehong; Liu, Aihua; Song, Yang; Li, Cunjiang; Gao, Ran; Wang, Lin; Wu, Liyong; et al. (Frontiers in Immunology, 2021)
Background: Myelin oligodendrocyte glycoprotein-antibody (MOG-ab)-associated disease (MOGAD) has highly heterogenous clinical and imaging presentations, in which encephalitis is an important phenotype. In recent years, some atypical presentations in MOG-ab-associated encephalitis (MOG-E) have been increasingly reported, but have not yet been described well. The aim of the study was to describe the clinical and imaging features of patients with MOG-E in our center. Atypical phenotypes would be reported, which is expected to expand the spectrum of MOGAD. Methods: We reviewed medical records of 59 patients with MOGAD diagnosed in our center and identified cases who had ever experienced encephalitic symptoms. 310 patients with autoimmune encephalitis (AE) were also reviewed and cases with positive MOG-ab were identified. Besides, patients with chronically progressive encephalitis were identified from 13 MOG-E and 310 AE patients. We collected demographic, clinical, laboratory, radiological and outcome data to explore clinical and imaging characteristics in MOG-E, especially the atypical phenotype of chronically progressive encephalitis. Results: We identified 13 patients (7 males, 6 females) with MOG-E. The median age at onset was 33 years (range 13~62 years). Most (9/13, 69.2%) of patients showed acute or subacute onset of encephalitic symptoms. Brain MRI abnormalities were observed in all patients. The most common lesion locations on MRI were cortical/subcortical (11/13, 84.6%), deep/periventricular white matter (10/13, 76.9%) and corpus callosum (4/13, 30.8%). Brain MRI patterns were categorized into four phenotypes. The most common pattern was cortical encephalitis with leptomeningeal enhancement/brain atrophy (11/13, 84.6%). Eight (8/13, 61.5%) patients had a good response to immunotherapy. Four (4/13, 30.8%) patients with chronically progressive course were identified from MOG-E cohort. They showed leukodystrophy-like pattern, multifocal hazy lesions or cortical encephalitis on MRI. With immunotherapy, they only showed mild or no improvement. We also identified four (4/310, 1.3%) patients with chronically progressive course from AE cohort. They had better outcomes than counterparts in MOG-E. Conclusions: This study demonstrates that encephalitic presentations in MOGAD had complex clinical patterns. Chronically progressive encephalitis may be a new phenotype of MOGAD. We recommend to test MOG-ab in subacute and chronic progressive dementia with leukodystrophy-like MRI lesions.